Which factors influence the activity levels of individuals with traumatic brain injury when they are first discharged home from hospital?. (6th December 2015) - Hamilton, Megan; Williams, Gavin; Bryant, Adam; Clark, Ross; Spelman, Tim
Abstract: Primary objectives : To determine the predictors of physical activity levels (PALs) of people with traumatic brain injury (TBI) during the transition from hospital to home. Research design : A prospective cohort study. Participants : Twenty-three individuals with TBI, consecutively admitted to TBI inpatient rehabilitation, who had independent community mobility potential on inpatient discharge. Methods and procedures : PALs (steps per day) were monitored at three time points: (T1) final week of inpatient rehabilitation, (T2) first week at home and (T3) 6 weeks following discharge. Measures across the physical, emotional and cognitive domains were performed at T1 and compared with PALs at T3. Results : PALs decreased significantly on hospital discharge (T2), compared to T1, and remained below recommended guidelines for maintenance of health and wellbeing at 6 weeks post discharge (T3). Motivation to exercise was the primary predictor of PALs at T3 ( p < 0.01), with fatigue ( p < 0.05) and anxiety ( p < 0.05) also being significantly associated. Measures of physical ability were not correlated with PALs at T3. Conclusions : PALs decreased significantly on discharge from hospital and remained below inpatient levels despite physical capacity for higher PALs. Motivation, fatigue and anxiety were important influencers of PALs during the transition home period.